2012
DOI: 10.2119/molmed.2011.00390
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Traumatic brain injury (TBI) and hemorrhagic shock often occur concomitantly due to multiple injuries. Gastrointestinal dysfunction occurs frequently in patients with TBI. However, whether alterations in the gastrointestinal system are involved in modulating neuronal damage and recovery after TBI is largely neglected. Ghrelin is a "gut-brain" hormone with multiple functions including antiinflammation and antiapoptosis. The purpose of this study was to determine whether ghrelin attenuates brain injury in a rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In the case of TBI, the role of UCP2 would be of acute compensation, potentially mitigating damage enough to allow cellular recovery in cases where UCP2 is not overwhelmed. Exemplifying this mechanism is ghrelin, which has been shown to be neuroprotective in the context of TBI through a mechanism reminiscent of ischemic preconditioning, resulting in increased UCP2 expression and greater neuroprotection [ 7 , 8 , 65 , 66 ]. In contrast, ghrelin’s counterpart leptin has been shown to have more acute UCP2-dependent mitochondrial stabilization effects in thalamic neurons [ 64 , 67 ].…”
Section: Physiology Of Ucp2mentioning
confidence: 99%
“…In the case of TBI, the role of UCP2 would be of acute compensation, potentially mitigating damage enough to allow cellular recovery in cases where UCP2 is not overwhelmed. Exemplifying this mechanism is ghrelin, which has been shown to be neuroprotective in the context of TBI through a mechanism reminiscent of ischemic preconditioning, resulting in increased UCP2 expression and greater neuroprotection [ 7 , 8 , 65 , 66 ]. In contrast, ghrelin’s counterpart leptin has been shown to have more acute UCP2-dependent mitochondrial stabilization effects in thalamic neurons [ 64 , 67 ].…”
Section: Physiology Of Ucp2mentioning
confidence: 99%
“…In our study, ICH mice exhibited a marked drop in body weight from two to 14 days compared with sham mice; however, treatment with ghrelin significantly attenuated the weight loss caused by ICH, indicating ghrelin could induce weight gain and better nutritional status in mice [46,47]. Nutritional status has a substantial impact on the immunity and prognosis of brain injury patients.…”
Section: Discussionmentioning
confidence: 89%
“…However, the impact of ghrelin administration on growth hormone, insulin, appetite, and metabolism in ICH requires further investigation. Recently, ghrelin has been documented to exert neuroprotection in several models of neurologic diseases, including ischemic stroke [51], TBI [47], and SAH [52]. More interestingly, studies on the effects of ghrelin on ischemic stroke [51] and TBI [47] indicated that ghrelin-mediated alleviation of brain injury contributed to the prevention of weight loss after brain insults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present report we hypothesized that ghrelin administration can prevent CI-induced cerebro-vascular impairment and intracranial hemorrhage and by these means can contribute to the amelioration of morbidity and mortality in sequelae of the illness. The rationale is that (i) firstly, the brain is one of the most highly perfused organs in the body and therefore, along with lung, has the most extensive microvascular network; (ii) secondly, numerous data suggest that while IR-induced endothelial apoptosis can “directly” disturb the blood–brain barrier, the vascular reactive response to the delayed bacteremia and sepsis can provoke intraparenchymal hemorrhage; (iii) thirdly, while ghrelin is defined as a gastrointestinal hormone that is primarily synthesized and secreted by the stomach, ghrelin is also expressed in the endothelial cells of blood vessels [ 24 , 25 , 26 , 27 , 28 ]; and (iv) fourthly, in vivo ghrelin production is shown to be dramatically affected by irradiation and CI [ 17 ]. Thus, so far along with its other physiological effects such as (i) stimulation of growth hormone release from the anterior pituitary gland and hypothalamus; (ii) induction of a positive energy balance; (iii) stimulation of neurogenesis and neuroprotection against damage due to ischemia, traumatic brain injury and neuromediator excitotoxicity; and (iv) suppression of sepsis and protection of vascular endothelium against septic inflammation, ghrelin has been also demonstrated to sustain endothelial function and angiogenesis [ 17 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%